2013
DOI: 10.1016/j.jsha.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive oil supplementation on PAI-1 expression in old rats

Abstract: Background: Although Mediterranean diet has grown worldwide due to its link with lower cardiovascular disease rate and greater longevity, the effect of olive oil, which is the principal component of Mediterranean diet, on plasminogen activator inhibitor-1 (PAI-1) concentrations in aged rats is not clear. This study was performed on 28 aged male Wistar albino rats allocated into two groups (14 rats each): Olive oil-treated group and the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…It was shown that olive oil intake reduced PAI-1 gene expression in aged Wistar rats (Nassef, Youssef, Louka, & Habib, 2013). In our study, ADR-induced fibronectin overexpression has been completely abolished after OLE without changing the level of TGF-β protein expression.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It was shown that olive oil intake reduced PAI-1 gene expression in aged Wistar rats (Nassef, Youssef, Louka, & Habib, 2013). In our study, ADR-induced fibronectin overexpression has been completely abolished after OLE without changing the level of TGF-β protein expression.…”
Section: Discussionsupporting
confidence: 63%
“…The level of angiotensin II is increased in SHR (Fan et al, 2014), thus we suggest that increased fibronectin level in the kidney of SHR with ADR‐induced FSGS could be at least in part mediated by RAS induction of PAI‐1, independently of TGF‐β. It was shown that olive oil intake reduced PAI‐1 gene expression in aged Wistar rats (Nassef, Youssef, Louka, & Habib, 2013). In our study, ADR‐induced fibronectin overexpression has been completely abolished after OLE without changing the level of TGF‐β protein expression.…”
Section: Discussionmentioning
confidence: 99%